The reinsertion of agronomy in the pos conflict (2016)
The purpose of this essay is to make known one of the hardest problems, which is currently crossing our country, the armed conflict. With a focused look and entering to analyze the impact of the conflict in the rural sector (field). The quest for lasting peacebuilding in this process is what we know as post-conflict. It will take into account different situations and events that have become common in the field. With all this, it is intended to have an analytical perspective subject to the new changes of reality; Consolidating the incorporation of those affected to where they were actually removed to belong to an armed conflict. One of the problems that is being discussed with the greatest growth is precisely the processes towards the construction of durable and post-conflict peace in Colombia, this has happened for a long time and the problem is to overcome this stage with support from the government Where progress and tools are given to the people who are entering their new life, giving them the necessary tools to be able to compete in the agricultural sector, ensuring that the tools and processes provided are competitive and can generate growth in the agricultural sector level . The territorial domination of some areas in Colombia have an economic interest of exploitation and businesses outside the law for these armed groups and the objective is that they will return to be part of a beneficial economic cycle for these zones and generate a positive growth. That is why we see it important and necessary to make the incorporation of the people in the conflict reorganize in society.